Effect of rainfed and irrigated conditions on yield and quality traits of new-improved sunflower (Helianthus annuus) hybrids in a sub-humid climate - OZ, MEHMET; KARASU, ABDULLAH; KUSCU, HAYRETTIN; SINCIK, MEHMET; TURAN, Z METIN; GOKSOY, A TANJU (The Indian Journal of Agricultural Sciences, 2013)
The study was carried out to compare the effects of a rainfed (non-irrigated) and irrigated conditions on yield, certainyield components and quality traits of new-improved sunflower (Helianthus annuus L.) hybrids in southern MarmaraRegion, Turkey having a sub-humid climate. Over two years (2006 and 2007), significant differences for all charactersexcept plant height and crude oil per-cent were found between irrigation regimes (irrigated and non-irrigated conditions)while genotypes showed significant differences for all characters investigated. Also, genotype × irrigation regime interactionwas highly significant for all traits except crude oil percent. In addition, year × irrigation regime, year × genotype and year× genotype × irrigation regime interactions were statistically significant for head diameter, 1 000 seed weight, seed yieldand crude oil yield. The seed yield and crude oil yield increased highly with irrigations. The seed yield increases forirrigated treatment compared with non-irrigated treatment were 58.3 % in 2006 and 101.4 % in 2007. Compared with non-irrigatedtreatment, crude oil yield increases for irrigated treatments were 56.9 % in 2006 and 99.4 % in 2007. Differencesbetween genotypes in seed yield and crude oil yield significantly varied according to irrigated and non-irrigated conditions.The control variety, Sanay and experimental hybrid, C 10 × R 10 produced more seed yield and crude oil yield than thoseof others in irrigated conditions, whereas highest seed yield and crude oil yield was obtained from the control variety,Muson in non-irrigated condition and differences among other hybrids were not statistically significant under rainfedcondition.